2011
DOI: 10.1007/s00425-011-1536-3
|View full text |Cite
|
Sign up to set email alerts
|

Presence of supercooling-facilitating (anti-ice nucleation) hydrolyzable tannins in deep supercooling xylem parenchyma cells in Cercidiphyllum japonicum

Abstract: Xylem parenchyma cells (XPCs) in trees adapt to subzero temperatures by deep supercooling. Our previous study indicated the possibility of the presence of diverse kinds of supercooling-facilitating (SCF; anti-ice nucleation) substances in XPCs of katsura tree (Cercidiphyllum japonicum), all of which might have an important role in deep supercooling of XPCs. In the previous study, a few kinds of SCF flavonol glycosides were identified. Thus, in the present study, we tried to identify other kinds of SCF substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
6
11
0
Order By: Relevance
“…The significantly lower INA in the autoclaved treated leaf sheaths (Table ) could result from sucrose (Gusta et al, ), tannin (Wang et al, ), flavanol glycoside (Kasuga et al, ), and/or arabinoxylan (Olien, ) in the leachate. The INA of tissues in the autoclave/water treatment group was comparable with the INA of nonacclimated excised crowns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significantly lower INA in the autoclaved treated leaf sheaths (Table ) could result from sucrose (Gusta et al, ), tannin (Wang et al, ), flavanol glycoside (Kasuga et al, ), and/or arabinoxylan (Olien, ) in the leachate. The INA of tissues in the autoclave/water treatment group was comparable with the INA of nonacclimated excised crowns.…”
Section: Resultsmentioning
confidence: 99%
“…The significantly lower INA in the autoclaved treated leaf sheaths (Table 5) could result from sucrose (Gusta et al, 2004), tannin (Wang et al, 2012), flavanol glycoside (Kasuga et al, 2008), and/or arabinoxylan (Olien, 1965) 3.6 | Three distinct freezing events in the cold-acclimated crown…”
Section: Initial Freezing Event In the Leaf Sheathmentioning
confidence: 99%
“…3, Table 3). The increase in digalloylglucose derivative at the end of winter (March) might be related to its antioxidant properties [61] and/or to its capacity to inhibit ice nucleation of water, facilitating an adaptation to freezing temperatures, as suggested for the boreal hardwood Cercidiphyllum japonicum S.& Z. by Wang et al [62].…”
Section: Discussionmentioning
confidence: 95%
“…Based our results, Kasuga et al 2008 found that some flavonol glycosides isolated from the xylem parenchyma cells had a high level of SFC activity. Furthermore, the hydrolyzable tannins in deep supercooling xylem cells in Cercidiphyllum japonicum exhibited the SFC activity like flavonol glycosides Wang et al, 2012 . As the cells of the katsura tree have been able to maintain a deep cooling state by accumulating some active compounds, we could predict that some compounds accumulated in other plants tissues or cells have similar activities.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, four kinds of flavonol glycosides with anti-ice nucleation activity have an important role in supercooling in the xylem parenchyma cells of katsura trees Cercidiphyllum japonicum Kasuga et al, 2008 . Furthermore, four kinds of hydrolysable gallotannins in the xylem parenchyma cells of katsura trees exhibited supercooling capabilities in the range of 1.5-4.5 , at a concentration of 1 mg/mL Wang D. et al, 2012 . The ability to avoid freezing like that of the katsura tree is due to low molecular weight compounds less than MW 500 like various polyphenols.…”
Section: The Preparation Of the Extract From Coffee Refusementioning
confidence: 99%